Power Losses Caused by Load Imbalance in the Central Building of PGRI Semarang University - Muhammad Zaenal Arifin; Muhammad Amiruddin; Margono Margono (Universitas PGRI Semarang, 2023)
The use of energy is basically very much needed in everyday life. Energy that is widely used is electrical energy, because electricity is one of the important factors in human life. Some electrical energy producers, in the country use fossil fuel sources such as coal and petroleum, and fossil energy is not renewable. Therefore, the government through the Regulation of the Minister of Energy and Mineral Resources number 14 of 2012 regulates energy management to control energy consumption in order to achieve effective and efficient energy utilization. PGRI Semarang University [L1] as an academic institution uses a lot of non-linear loads for administrative, teaching, laboratory and other supporting activities. Based on the analysis of data obtained at the Center Building of PGRI Semarang University experiencing an imbalance, the condition is not in accordance with the standards and risks increasing power losses. Seeing these conditions, recommendations were obtained that can be implemented at the Center Building of PGRI Semarang University, namely, balancing the load of phases R, S, T to reduce current imbalances. From the load imbalance, there were power losses on the neutral wire of 889,363 kW and power usage for one day in the R, S, T phases of 15,497,991 kW